The prevalence of condom use among university students in Zimbabwe: implications for planning and policy - Nkomazana, Njabulo; Maharaj, Pranitha (Cambridge University Press, 2016)
Young people, especially university students, are at high risk of HIV infections because of little or no parental or administrative prohibitions in campus environments. The aim of this study was to ascertain the level of condom use among university students in Zimbabwe; that is, condom use at last sex and consistent condom use among both regular and casual partners.The study draws on self-completed questionnaires administered to university students. The results reveal that, while 78.3% of sexually active respondents had used condoms in penetrative sexual encounters before, only 56.2% had used condoms at their last sexual encounter. As expected, consistent condom use was lower in regular sexual partnerships than it was in casual partnerships (30.6% versus 54.6%). Condom use at first sex and high personal HIV risk perception were found to be the most important factors in explaining condom use at last sex and consistent condom use with casual partners. Condom use intentions were high, as 75% of respondents indicated that they would use condoms at their next sexual encounters. Whilst this is commendable, use rates should ideally be higher still. Campus HIV/AIDS programmers should endeavour to ensure that condoms are available at all times in order to help translate these intentions into actual condom use. In addition, promotional programmes should encourage those who have not yet initiated sexual intercourse to use condoms at their first sex and also to improve personal HIV risk perceptions in order to trigger initiation of protective sexual behaviours.